Investigation of Toxic Effect of Ethanolic Extract of Carthamus tinctorius Seeds on Spermatogenesis in Male Rats: Pharmaceutical Science-Pharmacology for Better Medicial Drug - Himanshu Gupta; Dinesh Kumar Sharma; Kamal Kishore Maheshwari (International Journal of Life Science and Pharma Research, 2022)
Carthamus tinctorius (Family: Asteraceae) is a medicinal plant and many reported for the treatment of different diseases namely hypertension, arthritis, neurological, kidney disorders, etc. The higher dose (500 mg/kg) or long-term use of herbal medicines may cause serious toxic effects. The toxicity of the medicinal plant is an important concern to the researchers, and they investigate the harmful effects of the natural products for the safety purpose. Hence, the present study was aimed to assess the toxic effects of ethanolic extract (Containing semipolar and polar phytoconstituents) of Carthamus tinctorius seeds on spermatogenesis of rats. The seeds of Carthamus tinctorius collected from Bareilly, India. The ethanolic extract was prepared from Carthamus tinctorius seeds by macerating with 70% ethanol, and extract obtained was used for further studies. The ethanolic extract of Carthamus tinctorius was administered to rats at the dose of 100 mg/kg and 200 mg/kg for 45 days, and its toxic effect was determined by assessing the autopsy, body weight, testis, epididymis, seminal vesicle, number of pups, litter weight, serum testosterone, sperm motility and sperm count. The testis were isolated from the exploratory animals for the histopathological studies. The rats treated with the extract showed significant alteration in the autopsy, body weight, testis, epididymis, seminal vesicle, number of pups, litter weight, serum testosterone, sperm motility and sperm count compared to the control group of experimental animals. The histopathological observation of extract treated rats showed variations in testis morphology, supporting the failure in spermatogenesis. The findings concluded that the Carthamus tinctorius extract has a toxic effect on the rat testicular tissues without any signs of clinical toxicity.